PENGEMBANGAN ALAT EVALUASI BERBASIS WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA - Anisa Bela Febriani; Hanif Amrulloh; Lutfi Fadilah (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
The selection of this evaluation tool has considerations. For example, learning materials, facilities or facilities available at school, so that the learning objectives that have been set can be achieved. This can be facilitated by developing a wordwall-based interactive learning evaluation tool on pancasila education subjects, material on pancasila values.”This research is“R&D research wich refers to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model."The research subjects were 23 class III A” students in s trial at MI NU Metro, Lampung. “Validation carried out by material experts scores, namely 94% from media experts and 82% from material experts. Trials with student showed a significant increase in learning outcomes, with the averge score increasing from 75% (Pre-test) to 88% (Post-test). Feedback from teachers and student shows that wordwall based evaluation tools are practical, effective, and engaging. And can be deelared “Very Suitable” for use with class III A MI NU students to improve learning outcomes.